2020
DOI: 10.1080/2374068x.2020.1829959
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumour Detection and Grading Using Raman Scattering: Analogy from Semiconductors for Solving Biological Problem

Abstract: Subtle changes in Raman spectral line shape have been observed from malignant human brain cells and its possibility for being used in detection and grading of Glioma has been explored here. The latter has been developed as a result of the fact that the width of the Raman spectra is more sensitive, as compared to the peak position, to the brain tumours. The perturbations induced by the cell modification, as a consequence of the cancerous growth, may be responsible for the width's variation in the Raman spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…It is important here to mention that the Raman line shape, and associated symmetry, is sensitive to any perturbation in the system. 47 , 48 To dig out any possible interaction present at the microscopic level, Raman spectra have been recorded using 633 nm, and Raman line shape parameters have been extracted. Figure 2 shows the spectrum (red curve), recorded using 633 nm excitation, with E 1 2g (378 cm –1 ) and A 1g (404 cm –1 ) modes having an asymmetry ratio (α R ) of 1.4 and 0.7, respectively, estimated using the formula defined above.…”
Section: Resultsmentioning
confidence: 99%
“…It is important here to mention that the Raman line shape, and associated symmetry, is sensitive to any perturbation in the system. 47 , 48 To dig out any possible interaction present at the microscopic level, Raman spectra have been recorded using 633 nm, and Raman line shape parameters have been extracted. Figure 2 shows the spectrum (red curve), recorded using 633 nm excitation, with E 1 2g (378 cm –1 ) and A 1g (404 cm –1 ) modes having an asymmetry ratio (α R ) of 1.4 and 0.7, respectively, estimated using the formula defined above.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the presence of characteristic peaks of NiO, TiO 2 and NiTiO 3 confirms the synthesis of TiO 2 and the NiTiO 3 complex. To further confirm the chemical compositional characteristics, Raman spectroscopy is done (Figure d). The Raman spectra of m-NTTO reveal the presence of peaks at 154 and 206 cm –1 (marked by #), 310, 609, 708, and 758 cm –1 (marked by *), and 1060 cm –1 (marked by $).…”
Section: Resultsmentioning
confidence: 99%
“…Different physical conditions [ 84 ] and concentrations of substances, such as salt, can lead to changes in the position of Raman shifts [ 85 ]. It has also been shown that, depending on the glioma grade, the tissue microenvironment affects the shift of Raman bands by up to 38% [ 86 ].…”
Section: Discussionmentioning
confidence: 99%